Study on the Precursors of Coal-Rock Fracture Based on the Maximum Lyapunov Exponent of Acoustic Emission Parameters. (18th March 2022) - Cheng, Guoqiang; Sun, Xiaohui; Li, Jiangong
Abstract : In this paper, the relationship between acoustic emission (AE) parameters and coal-rock fracture is investigated by using the discrete element particle flow simulation software PFC. PFC is used to simulate the coal-rock uniaxial compression test for extracting the time series of AE event number, calculate the maximum Lyapunov exponent of the time series, and analyze the chaotic characteristics of AE event number. Combined with the relationship between the maximum point of the Lyapunov exponent and the peak point of the stress-strain curve, the coal-rock fracture precursor model was developed. The results indicate that during the uniaxial compression of coal-rock, the number of AE events first increases and then decreases, while the maximum point appears after the peak point of the stress-strain curve. The lower the coal-rock homogeneity, the earlier is the initial occurrence time of AE events. The AE event number has chaotic characteristics. In most cases, the chaotic characteristics of the number of AE events are the most evident before the specimen is completely destroyed. When the maximum Lyapunov exponent of AE event number time series mutates, it indicates that the specimen is about to be destroyed entirely, which can be used as a precursor criterion for coal-rock fracture.